Autophagy modulators from traditional Chinese medicine: Mechanisms and therapeutic potentials for cancer and neurodegenerative diseases. (24th December 2016) - Wang, Sheng-Fang; Wu, Ming-Yue; Cai, Cui-Zan; Li, Min; Lu, Jia-Hong
Abstract: Ethnopharmacological relevance: Traditional Chinese medicine (TCM), an ancient yet still alive medicinal system widely used in East Asia, has played an essential role in health maintenance and diseases control, for a wide range of human chronic diseases like cancers and neurodegenerative diseases. TCM-derived compounds and extracts attract wide attention for their potential application as therapeutic agents against above mentioned diseases. Aim of review: Recent years the enthusiasm in searching for autophagy regulators for human diseases has yielded many positive hits. TCM-derived compounds as important sources for drug discovery have been widely tested in different models for autophagy modulation. Here we summarize the current progress in the discovery of natural autophagy regulators from TCM for the therapeutic application in cancer and neurodegenerative disease models, aiming to provide the direct link from traditional use to new pharmacological application. Methods: The present review collected the literature published during the recent 10 years which studied the effect of TCM-derived compounds or extracts on autophagy regulation from PubMed, Web of Science, Google Scholar and Science Direct. The names of chemical compounds studied in this article are corresponding to the information in journal plant list. Results: In this review, we give a brief introduction about the autophagy and its roles in cancer and neurodegenerative disease models and describe the molecular mechanisms of autophagy modulation. We also make comprehensive lists to summarize the effects and underlying mechanisms of TCM-derived autophagy regulators in cancer and neurodegenerative disease models. In the end of the review, we discuss the current strategies, problems and future direction for TCM-derived autophagy regulators in the treatment of human diseases. Conclusions: A number of data from in vivo and in vitro models indicated TCM derived compounds and extracts hold great potential for the treatment of human diseases including cancers and neurodegenerative diseases. Autophagy, as a novel and promising drug target involved in a wide range of human diseases, can be modulated by many TCM derived agents, indicating autophagy modulation may be an important mechanism underlying the therapeutic effect of TCM in treating diseases. Furthermore, we look forward to seeing the discovery of ideal autophagy modulators from TCM with considerably higher selectivity for the treatment of human diseases. Graphical abstract: